Tracking the Will to Attend: Cortical Activity Indexes Self-Generated, Voluntary Shifts of Attention - Gmeindl, Leon (Atten Percept Psychophys, 2016)
The neural substrates of volition have long tantalized philosophers and scientists. Over the past few decades, researchers have employed increasingly sophisticated technology to investigate this issue, but many studies have been limited considerably by their reliance on intrusive experimental procedures (e.g., abrupt instructional cues), measures of brain activity contaminated by overt behavior, or introspective self-report techniques of questionable validity. Here, we used multivoxel-pattern time-course analysis of functional magnetic resonance imaging data to index voluntary, covert perceptual acts—shifts of visuospatial attention—in the absence of instructional cues, overt behavioral indices, and self-report. We found that these self-generated, voluntary attention shifts were time-locked to activity in the medial superior parietal lobule, supporting the hypothesis that this brain region is engaged in voluntary attentional reconfiguration. Self-generated attention shifts were also time-locked to activity in the basal ganglia, a novel finding that motivates further research into the role of the basal ganglia in acts of volition. Remarkably, prior to self-generated shifts of attention we observed early and selective increases in activation of medial frontal (dorsal anterior cingulate) and lateral prefrontal cortex (right middle frontal gyrus)—activity that likely reflects processing related to the intention or preparation to reorient attention. These findings, which extend recent evidence on freely chosen motor movements, suggest that dorsal anterior cingulate and lateral prefrontal cortices play key roles in both overt and covert acts of volition, and may constitute core components of a brain network underlying the will to attend.